Can someone please help me I really need it
2 answers:
Check the picture below
notice, both triangles are 45-45-90 triangles, so if one has a base of 26, so does the other
Download the app Slater! You put in the title of any text book and it'll pop up.
You might be interested in
Here ya go!!! this should be correct
Answer: answer in pic
55.2
Plz mark me brainliest
Answer:
![\large\boxed{-c^2(3c-2)=-3c^3+2c^2}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7B-c%5E2%283c-2%29%3D-3c%5E3%2B2c%5E2%7D)
Step-by-step explanation:
![-c^2(3c-2)\qquad\text{use the distributive property}\ a(b+c)=ab+ac\\\\=(-c^2)(3c)+(-c^2)(-2)\\\\=-3c^3+2c^2](https://tex.z-dn.net/?f=-c%5E2%283c-2%29%5Cqquad%5Ctext%7Buse%20the%20distributive%20property%7D%5C%20a%28b%2Bc%29%3Dab%2Bac%5C%5C%5C%5C%3D%28-c%5E2%29%283c%29%2B%28-c%5E2%29%28-2%29%5C%5C%5C%5C%3D-3c%5E3%2B2c%5E2)
Answer: −10−11i
Simplify the expression
Answer:
a. {(0, 7), (-1, 6)}
Step-by-step explanation:
![y = x^{2} +2x+7\\y=x+7](https://tex.z-dn.net/?f=y%20%3D%20x%5E%7B2%7D%20%2B2x%2B7%5C%5Cy%3Dx%2B7)
subtract the equations
![y = x^{2} +2x+7 \\- \ \ \ \ \ y=x+7\\y - y =x^{2} +2x+7-(x+7)\\0=x^{2} +x\\x = 0 \ and \ x= -1](https://tex.z-dn.net/?f=y%20%3D%20x%5E%7B2%7D%20%2B2x%2B7%20%5C%5C-%20%20%20%20%20%20%20%5C%20%5C%20%5C%20%5C%20%5C%20%20y%3Dx%2B7%5C%5Cy%20-%20y%20%3Dx%5E%7B2%7D%20%2B2x%2B7-%28x%2B7%29%5C%5C0%3Dx%5E%7B2%7D%20%2Bx%5C%5Cx%20%3D%200%20%5C%20and%20%5C%20x%3D%20-1)
for
, substitute x = 0
![y = (0)^{2} +2(0)+7\\y = 0 +0+7\\y=7](https://tex.z-dn.net/?f=y%20%3D%20%280%29%5E%7B2%7D%20%2B2%280%29%2B7%5C%5Cy%20%3D%200%20%2B0%2B7%5C%5Cy%3D7)
for
, substitute x = 0
![y = (-1)^{2} +2(-1)+7\\y = 1 -2+7\\y=6](https://tex.z-dn.net/?f=y%20%3D%20%28-1%29%5E%7B2%7D%20%2B2%28-1%29%2B7%5C%5Cy%20%3D%201%20-2%2B7%5C%5Cy%3D6)